2021
DOI: 10.3390/nu13092967
|View full text |Cite
|
Sign up to set email alerts
|

Trans Fatty Acids in Human Milk in Latvia: Association with Dietary Habits during the Lactation Period

Abstract: The human milk fatty acid, including trans fatty acid, composition is predominantly affected by the maternal diet. The aim of this research was to determine the trans fatty acid level in human milk among lactating women in Latvia, and to evaluate how maternal dietary habits affect the trans fatty acid composition of human milk. In total, 70 lactating women participated in this cross-sectional study. A 72-hour food diary and food frequency questionnaire were used to evaluate maternal dietary habits. Different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Obesity has been linked to increased delta-6 desaturase activity in numerous studies [ 74 , 75 ]. A significant positive correlation has been found between LA intake and LA levels in human milk [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity has been linked to increased delta-6 desaturase activity in numerous studies [ 74 , 75 ]. A significant positive correlation has been found between LA intake and LA levels in human milk [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trans fatty acids have been detected in breast milk, primarily vaccenic acid (C18:1 n-7), and elaidic acid (C18:1 n-9), which are associated with the consumption of milk and dairy products [ 35 ]. Trans fatty acid intake in lactating women usually depends on their geographical location and socio-economic situation.…”
Section: Introductionmentioning
confidence: 99%
“…The average TFA from the industrial process in the COL, TM and MM samples were 0.11%, 0.08% and 0.12%, respectively. Study carried out by Aumeistere et al (2021) in European women also observed levels of 0.10% of these FAs in BM, considered low values. This percentage found in our study may have occurred because the study participant received nutritional guidance while attending the nutrition/prenatal outpatient clinic and did not consume large amounts of industrialized foods such as margarine, vegetable creams, cookies, chips, ice cream, pastries, which are sources of TFA, according to the report during the consultation.…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, stearic acid was observed only in S 13 , S 14 , and S 15 at concentrations of 0.16, 0.66, and 0.37, respectively. Vaccenic acid is a natural trans-fatty acid thatis considered the main trans-fatty acid present in human milk [34]. Vaccinic acid (C18:1) was found in low amounts in the oils of the jojoba seeds of the various elite lines, ranging from 0.72 to 1.62%.…”
Section: Fatty Acid Profilementioning
confidence: 99%